2016
DOI: 10.1128/aem.03712-15
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cover Crop Species and Season on Population Dynamics of Escherichia coli and Listeria innocua in Soil

Abstract: dCover crops provide several ecosystem services, but their impact on enteric bacterial survival remains unexplored. The influence of cover cropping on foodborne pathogen indicator bacteria was assessed in five cover crop/green manure systems: cereal rye, hairy vetch, crimson clover, hairy vetch-rye and crimson clover-rye mixtures, and bare ground. Cover crop plots were inoculated with Escherichia coli and Listeria innocua in the fall of 2013 and 2014 and tilled into the soil in the spring to form green manure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 58 publications
(47 reference statements)
0
18
0
Order By: Relevance
“…Lower mean generic E. coli MPN/g values at the start of sampling for field B (DPS 1 and 7) were most likely less than 1.0 log 10 MPN/g because the sheep manure and residual cover crop were not tilled into the soil until DPS 10. Similar studies have hypothesised that tilling in cover crops in the spring in organic fields may contribute to increased bacteria populations in the soil (Reed‐Jones et al, ). And Hutchison et al () found that delaying incorporation of raw manure into the soil led to significantly faster decline rates for pathogens.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Lower mean generic E. coli MPN/g values at the start of sampling for field B (DPS 1 and 7) were most likely less than 1.0 log 10 MPN/g because the sheep manure and residual cover crop were not tilled into the soil until DPS 10. Similar studies have hypothesised that tilling in cover crops in the spring in organic fields may contribute to increased bacteria populations in the soil (Reed‐Jones et al, ). And Hutchison et al () found that delaying incorporation of raw manure into the soil led to significantly faster decline rates for pathogens.…”
Section: Discussionmentioning
confidence: 67%
“…Weekly farm management practices and environmental parameters were not tracked in detail over the entire period of this current study. However, a more cohesive collection of these parameters, as well as projects conducted throughout different seasons, might illuminate other associations related to the peaks of generic E. coli MPN/g in the soil, as suggested by various authors (Fraser et al, 2013;Gorski et al, 2011;Ongeng et al, 2014;Reed-Jones et al, 2016;Salaheen et al, 2015). Warmer temperatures and precipitation occurring in the spring and summer have been shown in past studies to be correlated with increased incidence and survival of foodborne pathogens in the environment (Fraser et al, 2013;Gorski et al, 2011).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In July and Aug. of 2015, no L. innocua was detected in any rye or rye-vetch plots. In contrast, Reed-Jones et al (2016) found that L. innocua in rye and rye-vetch plots can persist for the several weeks after inoculation, while a vetch monoculture and bare ground plots can show an immediate decline. In a different year of the same study, vetch monoculture and rye-vetch plots had significantly higher populations of soilborne L. innocua than rye monoculture plots.…”
Section: Discussionmentioning
confidence: 76%
“…During the winter in Iowa, soilborne L. innocua was capable of surviving, and was not affected by cover crop management. In Maryland, USA when organic fields were populated with L. innocua in the fall, the bacteria persisted and were recoverable the following spring (Reed-Jones et al, 2016). Contaminated water and animal manure are likely sources of human pathogens in produce fields.…”
Section: Discussionmentioning
confidence: 99%